2012
DOI: 10.21608/jfds.2012.81667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germination Process on the Chemical and Biological Active Compounds of Barley and Oat Grains

Abstract: In recent years, cereals especially barley and oat grains have attracted researches and commercial attention mainly due to their high contents of dietary fibers, βglucan and phenolic compounds with high antioxidant activates. Therefore, a preliminary study was carried out to estimate the components of raw barley and oat grains as well as, the effect of germination process on chemical composition and biological active compounds. The obtained results reveled that the germination process had a great role on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Oat grains subjected to germination were analyzed for mineral content and the results are depicted in Table 1. * Corresponding author's email: rmeenuspolia697@gmail.com Magnesium content increased from 169.55 to 187.25 mg/100 g, phosphorus from 429.61 to 454.61 mg/100 g, calcium from 4.70 to 7.72 mg/100 g, and iron from 4.70 to 7.72 mg/100 g. Our results are consistent with the findings of Refai et al (2012) who reported higher values of magnesium, calcium, zinc, and iron content in oats and barley grain subjected to soaking and germination (48 and 72 h). Further, the functional properties of oats flour were also affected after germination: bulk density decreased from 0.76 to 0.38 g/mL, water absorption capacity from 68.80% to 108.28%, and oil absorption capacity from 186.33% to 199.92 %.…”
Section: Resultssupporting
confidence: 90%
“…Oat grains subjected to germination were analyzed for mineral content and the results are depicted in Table 1. * Corresponding author's email: rmeenuspolia697@gmail.com Magnesium content increased from 169.55 to 187.25 mg/100 g, phosphorus from 429.61 to 454.61 mg/100 g, calcium from 4.70 to 7.72 mg/100 g, and iron from 4.70 to 7.72 mg/100 g. Our results are consistent with the findings of Refai et al (2012) who reported higher values of magnesium, calcium, zinc, and iron content in oats and barley grain subjected to soaking and germination (48 and 72 h). Further, the functional properties of oats flour were also affected after germination: bulk density decreased from 0.76 to 0.38 g/mL, water absorption capacity from 68.80% to 108.28%, and oil absorption capacity from 186.33% to 199.92 %.…”
Section: Resultssupporting
confidence: 90%
“…Donkor, et al (2012) reported that the radical scavenging activities of the phenolic extracts were between 13% and 73% for non-germinated and 14% and 53% for germinated of seven selected commercially important grains including wheat and sorghum. In contrary, Lo´pez-Amoro´s, et al (2006) found that peas and beans undergo a significant increase in antioxidant activity after germination, and El-Refai et al (2012) found also that the antioxidant activity was increased by increasing the germination period of barely and oats grains.…”
Section: Effect Of Soaking and Germination On Antioxidant Activitymentioning
confidence: 93%
“…In fact, the germination process is also one of methods used to improve the functionality of oat seed protein (Kaukovirta-Norja, et al, 2004). Recently, El-Refai et al (2012) found that germination process had positive effect to improve the bioactive compounds content as total phenolic anf flavonoids of barely and oat grains. In general soaking period was reported to have pronounced effects on the vitamin levels and anti-nutritional factors present in natural foods (Fadahunsi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…EL‐Refai et al . (2012) determined 0.99–5.11 gallic acid, 30.98–40.17 catechin 43.05–189.21 pyrogallol, 2.88–23.50 clorogenic acid, 0.72–2.46 ferulic, 1.02–6.38 mg/100 g syringic in raw and germination barley grain. It has been reported that after 120 h of germination, the amounts of phenolic compounds in oats increased more than 4‐fold compared to the control (Tian et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%